Private Pensions - A Viable Alternative? Distributive Effects of Private Pensions in a Comparative Perspective - Christina Behrendt (Luxembourg Income Study (LIS), 1999)
Pension reforms have been on the political agenda of governments and of international organisations as the OECD and the World Bank for some time. However, the strengthening of private elements in pension systems is often believed to intensify existing inequalities in the distribution of pensions among the population and to contribute to the marginalisation of large groups of the elderly. This paper explores the distributive effects of private pensions on the basis of LIS microdata for twelve industrialised welfare states. Its results confirm that private pensions indeed tend to produce specific inequalities, but also emphasise the importance of policy factors in mitigating the distributive effects of private pensions.
Keywords: 330; Private Altersvorsorge; Einkommensverteilung; Haushaltseinkommen; Lebensstandard; OECD-Staaten